(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Authors in this issue have grappled with the crises brought about the Covid-19 pandemic as they focus on a range of important topics about higher education. Writing from Turkey, Ghana, Nepal, India, the US, and the UK, they share perspectives from their contexts and disciplines.